Researching developing countries : a data resource guide for social scientist - Wright, Forrest D. (Chandos information professional series., 2016)
Why are some countries rich while others are poor? Why are some well governed while others experience frequent conflict? And how do you measure a country's true success anyways? Social scientists have attempted to answer these types of questions for decades, and have increasingly turned to data for this task. Researching Developing Countries: A Data Resource Guide for Social Scientists serves as a reference guide for social scientists and students interested in answering these complex questions. The book will also be helpful to librarians serving the social science disciplines. Topics covered in the book include: human development, economics, governance, conflict, demographics, migration and refugees, environment, foreign aid, energy and infrastructure, innovation and entrepreneurship, geography and urban development, and public opinion.